Ankle Joint Chronic Osteomyelitis: A Case Report and Updated Insights - Tika, Fanny Eprilia; Muhammad, Ismail; Eljatin, Dwinka Syafira; Adnyana, I Made Dwi Mertha (GLOBAL HEALTH SCIENCE GROUP, 2024)
Osteomyelitis is an infectious disease of the musculoskeletal system that can cause inflammation of the bones and joints caused by infectious agents. To date, there has been an increase in Osteomyelitis cases especially in individuals with comorbidities. The aimed of this study was to explore the frequent cases of chronic ankle joint osteomyelitis experienced by the public and provide new insights into the future treatment of this disease. In this study, we report the case of a patient with type 2 diabetes mellitus who developed osteomyelitis due to a wound caused by a scratch on a prickly pandanus leaf mat. A 58-year-old man presented to the emergency room with complaints of sores and pain, accompanied by swelling of the right foot. The wound on the leg oozed pus had an odor, and the patient had difficulty walking and fever for two weeks. Her hemoglobin level was 10 mg/dl, her leukocyte count was 20,040/µL, her current blood sugar level was 323 mg/dL, her 2-hour PP blood sugar level was 415 mg/dL, and her HbA1c level was 12. On foot examination, a CRT of < 2 s was found, and the degree of dorsal pedic artery pulsation was weak. An opaque area was observed in the ankle joint of the right foot, accompanied by a distal 1/3 epi-metaphyseal fracture of the right fibula bone with swelling, a distal 1/3 epiphyseal deformity of the right tibia bone, and a calcaneal spur on X-ray. Trauma and systemic risk factors such as diabetes mellitus were found in the patient, increasing the risk of worsening chronic osteomyelitis. The principles of osteomyelitis management include optimizing the patient's general condition; performing pharmacological debridement, reconstruction, and stabilization; and completing rehabilitation. Recent insights highlight the importance of a multidisciplinary approach, advanced diagnostic tools, antibiotic stewardship, novel therapies, and patient-centered care to improve outcomes for individuals affected by this challenging condition in the future.